Investigating Verbal Humor in Selected Mr. Iglesias Sitcom Shows Episodes - Nabila, Kafa Bella; Ena, Ouda Teda; Bram, Barli (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Humor can be found in people's daily life, movie, and stand-up comedy. People use it to criticize and entertain at the same time. In entertaining and criticizing a situation, humor can be in a form of a TV show or sitcom. This research focuses on verbal humor in a sitcom entitled Mr. Iglesias. This study aims to figure out the types of verbal humor using the General Theory of Verbal Humor (GTVH) by Attardo & Raskin (1991). This research examined five episodes of Mr. Iglesias’s shows from seasons 1 to 5 using a descriptive qualitative method. The results showed that this situation comedy has 58 expressions that employed linguistic humor. It could be classified into 8 of the 12 types of verbal humor. The six aspects of GTVH theory used to analyze the linguistic section were script opposition, logical mechanism, situation, target, narrative strategy, and language. Based on the six aspects of GTVH, this situational comedy indicated sarcasm as the most used verbal humor category.